Kirche, Geld und Seelenheil - Dieter Schmidtchen (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 1997)
Die Kirchen in Deutschland werden in diesem Essay als Multiproduktunternehmen analysiert, die sich in einer Krise befinden: die Kunden laufen weg, die Kirchensteuereinnahmen sinken. Ausgehend von der Idee, daß das Heilsversprechen ein knappes Gut ist, wird eine Empfehlung an die Kirchen entwickelt, sich nicht in der Konkurrenz zu sozialen Diensten aufzureiben. Die Konzentration auf ihre Kernkompetenz - die Produktion des Heilsversprechens - dürfte sie aus ihrer problematischen Situation herausführen. – – The churches in Germany are analyzed as multiproduct firms. Even though these enterprises raise their revenues in part through the tax system, they find themselves in a crisis: the number of customers is persistently decreasing. Starting with the idea that salvation is a scarce economic good, this essay develops a recommendation that the churches should abstain from competing with other social services. To concentrate on the production of salvation as their core comeptency might lead the churches out of their problematic situation.
Keywords: L21; 330; Economic Analysis of Religion; Multiproduct Enterprises; Core Competency; Religion; Kirche; Rationales Verhalten; Theorie; Deutschland